Shelf-life evalution of Agastyharitaki Avaleha and its granule: A preliminary study - Vasundhara Jaluthriya; Pravin Jawanjal; Prem Kumar Goud; B J Patgiri; P Bedarkar (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Shelf life is the indication of best before use duration, the importance of quality of package and storage condition is also emphasized in classics. Nowadays, due to the development and adaptation of packaging and storage technology by Ayurvedic industries, a need arise to restudy and re-establish the newer ones criteria. AIM AND OBJECTIVES: The aim and objectives of the study were to evaluate the shelf life of Agastyaharitaki Avaleha (AHA) and its granule prepared with Khanda Sharkara through accelerated stability study. SUBJECTS AND METHODS: Physicochemical parameters were measured at 40°C ± 2°C temperature and 75% ± 5% relative humidity. The analysis was repeated at intervals of 1, 3, and 6 months, and average 10% degradation of both the test drug samples was calculated and extrapolated to find the shelf life. RESULTS: Agastyaharitaki granule (AHG) prepared with Khanda Sharkara showed more extractive values and sugar contents and found to have a longer shelf life (5.28 years) than AHA?(1.57 years). AHG is comparatively more stable than AHA.